Nutritional assessment of school children and adolescents: Pokhara city in Western Nepal - Maskey, Manisha; Sharma Annavarapu, Laxminarasimha; Karmacharya, Poonam (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Nutritional assessment of school children and adolescent is one of the most cost-effective ways of keeping track of overall wellbeing of children in the society. The objective of this study was to find out the nutritional status of school children and adolescent of Pokhara city using anthropometric indicators.Method: A total of 1160 students from the schools across the Pokhara city, Nepal, were enrolled in this study. Anthropometric measurements, height and weight, mean height and weight for age, and BMI for age were estimated. Undernutrition and obesity were defined as per the 2007 WHO growth reference data. Association among the variables were determined by applying statistical tests: t-test and Anova.Result: Growth curve of weight and BMI for age were above 15th percentile and height for age were between 3rd and 15th percentile, in both, boys and girls. The proportion of stunted and underweight students were 26.29% (boys 51% and girls 41%) and 24.65% (boys 53% and girls 47%) respectively. The proportion of thin, severely thin, overweight and obese were 3.53%, 5.03%, 12.49% and 8.96% respectively. Father’s occupation and education, mother’s occupation, school type, number of siblings were statistically associated with mean BMI and height.Conclusion: Stunted and underweight were seen in a quarter of students, as well overweight and obesity in less than 10% of school children surveyed.